Emetine and Indirubin- 3- monoxime interaction with human brain acetylcholinesterase: A computational and statistical analysis - Ahmad, Syed Sayeed; Khan, Haroon; Khalid, Mohammad; Almalki, Abdulraheem SA (Cellular and Molecular Biology, 2022)
Alzheimer’s disease is a chronic neurodegenerative ailment and the most familiar type of dementia in the older population with no effective cure to date. It is characterized by a decrease in memory, associated with the mutilation of cholinergic neurotransmission. Presently, acetylcholinesterase inhibitors have emerged as the most endorsed pharmacological medications for the symptomatic treatment of mild to moderate Alzheimer’s disease. This study aimed to research the molecular enzymatic inhibition of human brain acetylcholinesterase by a natural compound emetine and I3M. Molecular docking studies were used to identify superior interaction between enzyme acetylcholinesterase and ligands. Furthermore, the docked acetylcholinesterase-emetine complex was validated statistically using an analysis of variance in all tested conformers. In this interaction, H-bond, hydrophobic interaction, pi-pi, and Cation-pi interactions played a vital function in predicting the accurate conformation of the ligand that binds with the active site of acetylcholinesterase. The conformer with the lowest free energy of binding was further analyzed. The binding energy for acetylcholinesterase complex with emetine and I3M was -9.72kcal/mol and -7.09kcal/mol, respectively. In the current study, the prediction was studied to establish a relationship between binding energy and intermolecular energy (coefficient of determination [R2 linear = 0.999), and intermolecular energy and Van der wall forces (R2 linear = 0.994). These results would be useful in gaining structural insight for designing novel lead compounds against acetylcholinesterase for the effective management of Alzheimer’s disease.